2017
DOI: 10.1098/rsif.2016.0851
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of oxygen tension within mesenchymal stem cell spheroids

Abstract: Spheroids formed of mesenchymal stem cells (MSCs) exhibit increased cell survival and trophic factor secretion compared with dissociated MSCs, making them therapeutically advantageous for cell therapy. Presently, there is no consensus for the mechanism of action. Many hypothesize that spheroid formation potentiates cell function by generating a hypoxic core within spheroids of sufficiently large diameters. The purpose of this study was to experimentally determine whether a hypoxic core is generated in MSC sphe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
120
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 116 publications
(133 citation statements)
references
References 58 publications
11
120
1
1
Order By: Relevance
“…However, in the last phase with massive cell death there was a rebounding of oxygenation ( Figure 5B), due to both decreased total cell consumption and to spheroid shrinkage (given that the size of dying cells was set to decrease with 50%). This was observed in the notable lack of a concentration gradient at the center of the domain with further development of the necrotic core, which measured consistently with in vitro work that demonstrate the interactions of diffusive nutrients and cell viability in spheroidal aggregates [34,35].…”
Section: Coupling Oxygenation and Cell Deathsupporting
confidence: 79%
“…However, in the last phase with massive cell death there was a rebounding of oxygenation ( Figure 5B), due to both decreased total cell consumption and to spheroid shrinkage (given that the size of dying cells was set to decrease with 50%). This was observed in the notable lack of a concentration gradient at the center of the domain with further development of the necrotic core, which measured consistently with in vitro work that demonstrate the interactions of diffusive nutrients and cell viability in spheroidal aggregates [34,35].…”
Section: Coupling Oxygenation and Cell Deathsupporting
confidence: 79%
“…We previously demonstrated that MSC spheroids do not exhibit a hypoxic core due to a nutrient gradient, perhaps due to adaptive reductions in matrix deposition and packing density with increases in spheroid diameter [35]. However, the entrapment of MSC spheroids in hydrogels likely reduces diffusion-mediated transport from that observed with free spheroids, altering the oxygen microenvironment and potentially upregulating hypoxia-adaptive signals even further.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to monolayer culture, MSCs aggregated into spheroids retain a supportive extracellular matrix (ECM) and engage in cell-cell contact that better recapitulates a native tissue environment. 10 Compared with monodispersed cells, spheroid formation can further potentiate cell survival 11 and secretion of endogenous growth factors, 12 motivating continued investigation into the mechanism and therapeutic effects of cell-cell communication within a spheroid. This complex network of communication is orchestrated via signals from the microenvironment such as paracrine or autocrine-acting soluble factors 13 and intercellular communication through gap junctions, extracellular vesicles, 14 and tunneling nanotubes (TNTs).…”
mentioning
confidence: 99%